Tropical oribatid mites in soil toxicity testing: Optimization of test protocol and the effect of two model chemicals (cadmium and dimethoate) on Muliercula inexpectata. (March 2019) - Owojori, Olugbenga J.; Ademosu, Oluwadamilare T.; Jegede, Olukayode O.; Fajana, Hamzat O.; Kehinde, Temitope O.; Badejo, Mosadoluwa A.
Abstract: The oribatid mite, Oppia nitens, has gained recognition in recent laboratory ecotoxicological tests, however, the species global distribution is limited to temperate regions and not ecologically relevant for tropical soils. The present study reports the first laboratory study aimed at assessing the ecotoxicity of contaminants with the tropical oribatid mite, Muliercula inexpectata . To develop the protocols, synchronized adult specimens of M. inexpectata were tested in a natural soil collected at the Teaching and Research Farm of the Obafemi Awolowo University, Ile-Ife, Nigeria. An optimization test was done using different soil quantities (5, 20, 40 g), durations (14, 21, 28 d) and temperature regimes (20, 22, 24, 26, and 28 °C). The results show M . inexpectata peak juvenile production at 28 d and temperatures of 24–26 °C in 20 g of soil. Test conditions were further optimized to assess the effects of cadmium and dimethoate on adult lethality and reproduction of M. inexpectata using 20 g of soil, with an exposure temperature of 26 °C for a duration of 28 d. The LC50 (survival) and EC50 (reproduction) values of cadmium for M. inexpectata were 46.55 (26.26–82.52) mg/kg and 15.61 (13.65–20.63) mg/kg, respectively. The LC50 and EC50 values of dimethoate for M. inexpectata were 7.57 (5.40–10.60) and 4.42 (0–7.16) mg/kg, respectively. Compared to other mite species, they are either more or less sensitive depending on the chemicals considered. The results of the present study demonstrate that M. inexpectata is a promising candidate for routine and ecologically-relevant ecotoxicological assessments in tropical regions. Highlights: Muliercula inexpectata is a promising test species from tropical regions. Test duration of 28 days, 20 g of soil and a temperature of 26 °C is adequate. The species has similar sensitivity to dimethoate as other oribatid mites. The species has higher sensitivity to Cd than similar oribatid mites.